Scientific Literacy in Hybrid Learning with the STEM Approach for the Students of Primary School Teacher Education - Santos, Belmira Sagrada Ferrao; Murti, Rahayu Condro; Limiansih, Kintan; Tahu, Gregorius Paulus (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Scientific literacy is essential in improving students' skills to deal with the rapid development of science and technology. This quantitative descriptive research aims to: obtain information about the scientific literacy skills of prospective elementary school teacher students in hybrid learning with a STEM approach at a university in Indonesia. The sampling technique in this research applied convenience sampling involving 101 students of semester two as the subjects. The scientific literacy of primary school teacher candidates was collected using a self-developed, multiple-choice questionnaire following the scientific literacy competence of PISA, and it has been validated, achieving a score of 3.50 (perfect category). The results of this research show that scientific literacy of the 2nd-semester students of the primary elementary school teacher department is categorized as low with an average value of competency one is 53.96% (low category), competency 2 is 56.19% (low category), and competency 3 of 63.61% (medium category) so that the overall average of the three competencies is 57.92% (low category). Following up on the findings of this research, the scientific literacy of primary school teacher candidates in hybrid learning with a STEM approach can be further optimized by paying attention to the design of lesson plans, learning modules, and the implementation of a STEM-based learning approach.